(untitled) (Research, Society and Development, 2022)
Introduction: Smoking is known to bring several harms, especially to the cardiovascular system. The electronic cigarettes (ECs), in turn, were created as an alternative to smoking cessation, however its safety and benefits are doubtful. Objective: Given the growing popularity of these devices, a literature review is sought to identify their possible adverse effects on the cardiovascular system of young people. Method: Searches were carried out in databases (Google Academic, BVS, SciELO, PubMed and EbscoHost) in an attempt to search for studies that correlate the use of electronic devices for smoking (EDS) by young people and damage to the cardiovascular system. Results: Among the articles reviewed, it was evidenced that there are cardiotoxic substances in the vapors of ECs, which are related to phenomena that result in a greater risk of cardiovascular diseases, such as increased oxidative stress, platelet activation and blood pressure and heart rate variation. In addition, there was an exponential increase in the use of EDS by adolescents, a greater chance of becoming a smoker when using these devices, as well as a greater chance of cardiovascular disease among dual EC and cigarette users. traditional. Conclusion: After analyzing 18 articles, there was a greater chance of developing cardiovascular diseases due to the use of ECs, which is more worrying in young people, since early exposure is associated with a greater chance of dependence. Therefore, considering the harm and uncertainties regarding ECs, it is recommended that young people be cautious when using these devices.